Phytase supplementation in Broilers: Influence on growth performance and physiological health - Md. Imranuzzaman; Hemayet Hossain; Faija Sadia Pory; Dipsana K.c.; Md Saidul Haque; Sanjida Akter; Papri Rani Dey; Md. Ashiqur Rahman; Md. Arif Ishtiaq Shovon; Md. Masudur Rahman; Md. Siddiqul Islam; Md. Mahfujur Rahman (Journal of Advanced Biotechnology and Experimental Therapeutics)
Phosphorus is essential for broiler growth and bone development, but its bioavailability from plant-based feed is restricted by phytate binding. Phytase supplementation enhances nutrient utilization by breaking down phytate, improving phosphorus availability, growth performance, gut health, and reducing environmental phosphorus excretion. Thus, this study aimed to evaluate the impact of phytase enzyme supplementation on growth performance and hemato-biochemical markers as a potential alternative to antibiotic growth promoters in broilers. In this study, 300 Arbor Acres broiler chicks were randomly assigned to five treatment groups (T0–T4) with three replicates each. The control group (T0) received a basic diet (1–42 days), while experimental groups T1 supplemented with oxytetracycline and T2–T4 were supplemented with Phytase (Natuphos® E) from days 7–42. T1 received oxytetracycline (1000 mg/kg), while T2, T3, and T4 were supplemented with 500, 750, and 1000 FTU/kg of Phytase, respectively. Growth performance was assessed through body weight, feed intake, feed conversion ratio (FCR), and livability. Blood samples were analyzed for hematological parameters (CBC) and biochemical markers, including total protein, albumin, ALT, AST, cholesterol, triglycerides, LDL, and HDL. Results indicated significant improvements in body weight and FCR in phytase-supplemented groups, with T4 showing the best performance (body weight 2915.1 g, FCR 1.53). Phytase supplementation improved hematological and biochemical profiles in broilers, with 1000 FTU/kg showing the highest efficacy. These data suggest that phytase enhances growth, feed efficiency, and physiological parameters, making it a viable alternative to antibiotic growth promoters. [ J Adv Biotechnol Exp Ther 2025; 8(2.000): 342-352]